Environmental drivers of bacterial community diversity in the rhizosphere soil of Zanthoxylum nitidum (Roxb.) DC from different origins and their correlation with bioactive compounds - Chen, Long; Huang, MeiRong; Wang, Hui; Huang, Bilei; Long, Hai; Simal-Gandara, Jesus; Zhu, Hua; Dai, Zhonghua; Zhang, Miao (Frontiers in Plant Science, 2025)
IntroductionThis study investigated the rhizosphere bacterial communities of Zanthoxylum nitidum(Roxb.) DC.MethodsUsing an integrated approach combining 16S rRNA sequencing, redundancy analysis (RDA), and grey relational analysis (GRA) to unravel the correlation among soil environmental factors, microbial diversity, functional potential, and key medicinal compounds.ResultsThis study revealed for the first time the effects of environmental factors such as soil pH, organic matter content (ORM), altitude(HT), soil sand(SP) and soil silt (SSG) on the diversity of soil bacterial community, annotated and analyzed the functions of differential flora, and established the correlation between 15 main differential flora (such as Rudaea, Bradyrhizobium, Gemmatimonas) and nitidine chloride, which is the main medicinal active component of Zanthoxylum nitidum(Roxb.) DC.DiscussionThis study provides theoretical basis and important reference for soil adaptability optimization of Zanthoxylum nitidum (Roxb.) DC cultivation from bacterial community regulation, and highlights the supporting value of the study for the sustainable development of medicinal plant resources.